Do subjects with minimal motor features have prodromal Parkinson disease?. Issue 3 (10th March 2018) - Chu, Yaping; Buchman, Aron S.; Olanow, C. Warren; Kordower, Jeffrey H.
Abstract : Objective: Understanding the pathological changes underlying mild motor features of the eldery and defining a patient population with prodromal Parkinson disease (PD) are of great clinical importance. It remains unclear, however, how to accurately and specifically diagnose prodromal PD. We examined whether older adults with minimal parkinsonian motor features have nigrostriatal degeneration and α‐synuclein pathology consistent with prodromal PD. Methods: Brain sections were obtained from older adults with a clinical diagnosis of PD (n = 21) and without a clinical diagnosis of PD (n = 27) who underwent motor examination proximate to death. Cases without PD were further dichotomized into no motor deficit (n = 9) or minimal motor features (n = 18) groups using a modified Unified Parkinson's Disease Rating Scale. We performed quantitative unbiased stereological analyses of dopaminergic neurons/terminals and α‐synuclein accumulation in the nigrostriatal system. Results: In all subjects with minimal motor features, there were significant reductions in dopaminergic neurons and terminals in the substantia nigra and putamen that were intermediate between subjects with no motor deficit and PD. Phosphorylated α‐synuclein inclusions were observed in the substantia nigra that were of similar density to what was seen in PD. Furthermore, there was greater Lewy neuritic pathology in the putamen relative to PD patients. Lastly, neurons with α‐synuclein inclusions displayed reductions in tyrosine hydroxylase expression that were comparable in subjects with both minimal motor features and PD. Interpretation: Minimal motor features in older adults may represent prodromal PD and identify at‐risk individuals for testing putative neuroprotective interventions that could slow or prevent PD progression. Ann Neurol 2018;83:562–574